Design of Plasmonic NOT Logic Gate Based on Insulator – Metal – Insulator (IMI) waveguides - Fakhruldeen, H. F.; Mansour, T. S. (Advanced Electromagnetics, 2020)
In this work, all-optical plasmonic NOT logic gate was proposed using Insulator-Metal-Insulator (IMI) plasmonic waveguides Technology. The proposed all-optical NOT gate is simulated and realized using COMSOL Multiphysics 5.3a software. Recently, plasmonic technology has attracted high attention due to its wide applications in all-optical signal processing. Due to its highly localization to metallic surfaces, surface plasmon (SP) may have huge applications in sub wavelength to guide the optical signal in the waveguides which results in overcoming the diffraction limit problem in conventional optics. The proposed IMI structure is consist of a dielectric waveguides plus metallic claddings, which guide the incident light strongly in the insulator region. Our design consists of symmetric nano-rings structures with two straight waveguides which based on IMI structure. The operation of all-optical NOT gate is realized by employing the constructive and destructive interface between the straight waveguides and the nano-rings structure waveguides. There are three ports in the proposed design, input, control and output ports. The activation of control port is always ON. By changing the structure dimensions, the materials, the phase of the applied optical signal to the input and control ports, the optical transmission at the output port is changed. In our proposed structure, the insulator dielectric material is glass and the metal material is silver. The calculated contrast ratio between (ON and OFF) output states is 3.16 (dB).